Parade - Crews, Donald (Albany, NY : Delmar Publishers, 1990)
Illustrations and brief text present the various elements of a parade--the spectators, street vendors, marchers, bands, floats, and the cleanup afterwards.
Keywords: Parades -- Juvenile literature; Parades